Control strategy for storm runoff in an urbanizing basin - Ye, Zhaoqing. (2009)
Almost all countries are experiencing urbanization to a more or less extent. The process brings new challenges and poses new problems to drainage design and flood control. In this study, the impact of urbanization on the hydrology of a typical drainage basin in Singapore is investigated. The HEC 1 computer model is employed for hydrologic simulations.